STRATEGI ADAPTASI MAHASISWA KRISTEN DI UNIVERSITAS ISLAM NEGERI SULTAN SYARIF KASIM RIAU - Mesra Diana; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This reseacrh was done in Sultan Syarif Kasim Islamic State University. This research’s aim is to know the strategy of christian students in Sultan Syarif Kasim Islamic State University. Thie kind of research is qualitative which was analized descriptively. The theory used in this research is ‘Adaptation Theory’ by Pierre Bourdieu. In this research there are six respondents. The sampling technique is Purposive Sampling. The result from the field of study said that the christian students often get some insinuations, but they don’t want to against them. Because they know that would make disruption or it would affect their college.Keywords: Strategy, Adaptation, Christian Students